Penanaman Pengetahuan Mitigasi Bencana Kebakaran Pada Siswa Sekolah - L.M. Azhar Sa'ban; Nastia; Sufiarni; L.M. Fakhri Mihzan Rabbani (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2023)
This research aims to determine the instillation of knowledge about fire disaster mitigation from an early age carried out by the Baubau City Fire and Rescue Service. The method used in this research is a qualitative method. The results of this research are that the Baubau City Fire and Rescue Service held training and education on fire disaster preparedness and response. This activity was divided into two sessions, the first session presented educational material introducing fire disasters, the second session focused on fire education and continued with a simulation of how to deal with fire disasters using basic fire extinguishers including wet sacks and light fire extinguishers (APAR). Apart from that, the Baubau City Fire and Rescue Service also provides a fire engine and allows students to ride it. Baubau City Fire and Rescue Service offers training to improve the skills of all students. When the Baubau City Fire and Rescue Service deploys resources in the school environment, it is important to know the steps that must be taken in the event of a disaster and the losses that will be suffered. The Baubau City Fire and Rescue Service routinely involves school students, local communities and other organizations to conduct outreach and training regarding fire prevention and management. This was done to reduce the number of fires that occurred in Baubau City.